2015
DOI: 10.1080/23796529.2015.11674725
|View full text |Cite
|
Sign up to set email alerts
|

Kids, take a look at this! Visual Literacy Skills in the School Curriculum

Abstract: Although the paradigm of visual literacy (VL) is rapidly emerging, the construct itself still lacks operational specificity. Based on a semiotic understanding of visual culture as an ongoing process of 'making meaning', we present in this study a skill-based classification of VL, differentiating four sets of VL skills: perception; imagination and creation; conceptualization; analysis. A qualitative curriculum analysis based on this framework revealed that curriculum standards for compulsory education in Belgiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In education, visual literacy is considered an important aspect of media literacy, which is the ability to critically analyse, evaluate, and produce media messages. By developing visual literacy skills, students can be better prepared to understand and interpret the visual messages they encounter in everyday life, as well as to effectively communicate their own ideas and information through visual means (39). Integrating art education into other subjects such as science, home science, language, mathematics, and music can enable students:…”
Section: Visual Literacymentioning
confidence: 99%
“…In education, visual literacy is considered an important aspect of media literacy, which is the ability to critically analyse, evaluate, and produce media messages. By developing visual literacy skills, students can be better prepared to understand and interpret the visual messages they encounter in everyday life, as well as to effectively communicate their own ideas and information through visual means (39). Integrating art education into other subjects such as science, home science, language, mathematics, and music can enable students:…”
Section: Visual Literacymentioning
confidence: 99%
“…In education, visual literacy is considered an important aspect of media literacy, which is the ability to critically analyze, evaluate, and produce media messages. By developing visual literacy skills, students can be better prepared to understand and interpret the visual messages they encounter in everyday life, as well as to effectively communicate their own ideas and information through visual means [39]. Integrating art education into other subjects such as science, home science, language, mathematics, and music can enable students:…”
Section: Visual Literacymentioning
confidence: 99%
“…It entails the acquisition of a set of abilities necessary to interpret the content of visual information, to evaluate, reflect, and to derive meaning from visuals (Metros, 2008). However, the research by Vermeersch and Vandenbroucke (2015) found that the need to understand and comprehend visual representations is only present in the curriculum in an outer way. Such a requirement exists in the field of education, where pupils should be taught visual literacy.…”
Section: Integration Of Visual Media In Music Lessonmentioning
confidence: 99%
“…Visual literacy can sometimes develop on its own, without much assistance from the instructor. Thus, according to Vermeersch and Vandenbroucke (2015), such spontaneous learning to understand visual representations typically leads to the development of lower order cognitive skills. Students must be taught visual literacy abilities in order to instill higher thinking skills in them.…”
Section: Integration Of Visual Media In Music Lessonmentioning
confidence: 99%